Structural properties and psychometric improvements of the Health Literacy Questionnaire in a Slovak population - Kolarcik, Peter; Cepova, Eva; Madarasova Geckova, Andrea; Elsworth, Gerald R; Batterham, Roy W; Osborne, Richard H (International journal of public health, 2017)
OBJECTIVES: Health literacy is an important determinant of health and health equity and therefore requires robust measurement. The aim was to examine the psychometric properties of the Slovak version of the Health Literacy Questionnaire (HLQ) including revised wording of response categories. METHODS: A cross-sectional survey of the general Slovak adult population (N = 360, mean age 39) was conducted with the HLQ following its translation and cultural adaptation. Psychometric tests (confirmatory factor analysis, Cronbach's alpha, composite reliability) and association (linear regression, ANOVA) with sociodemographic variables were undertaken. The performance of alternative version of response options were explored with the Mann-Whittney U test and item response theory. RESULTS: A highly restrictive nine-factor confirmatory factor analysis showed acceptable fit [χ 2WLSMV = 1684 (df = 866), p < 0.0001; CFI = 0.943, TLI = 0.938, RMSEA = 0.051, WRMR = 1.297] and reliability was acceptable (range 0.73-0.84). The revised response categories had a better distribution with lower average scores in three domains, compared with the original, and improved item information curves. CONCLUSIONS: The nine HLQ scales are robust, providing a fine-grained assessment of health literacy. The revised response options improve psychometric properties and are recommended for future studies.
Keywords: Cultural adaptation; lidé; mladiství; Adult; Middle Aged; Health literacy; Slovakia; zdravotní gramotnost; Female; průzkumy a dotazníky; kultura; Measurement; Health Literacy Questionnaire (HLQ); Culture; Adolescent; Humans; Item response theory; průřezové studie; Slovenská republika; Cross-Sectional Studies; Psychometrics; lidé středního věku; mužské pohlaví; Health Literacy; psychometrie; ženské pohlaví; Male; Aged; dospělí; Surveys and Questionnaires; senioři